2024
DOI: 10.1101/2024.01.16.575797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wastelands or Preferred-lands? Indicators for redefining Desert conservation

Manasi Mukherjee,
Dhriti Banerjee,
Indu Sharma
et al.

Abstract: Desert ecosystems though crucial in shaping global climate, are often perceived to have limited function and are frequently designated as wastelands due to low biotic diversity and abundance. We explore the functional properties of desert through assessment of spatio-temporal variations of avian species richness and insect abundance of the relatively understudied Thar in Rajasthan. The study was conducted across four contrasting ecoregions (Western Thar (WT), Eastern Thar (ET), Transitional Zone (TZ), and Cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Such biogeographic distribution patterns in birds are known to be correlated to the trophic niche breadth (Fargallo et al, 2022). However, our further investigation on geographic distinctness of desert through mapping avian biodiversity with observational data, revealed that trophic niches not only play a crucial role in determining regional diversity but also the influx of migratory species (Mukherjee et al, 2024). These migratory birds due to their wide distribution (Pereira and Cooper, 2006), sensitivity to environmental changes (Smits and Fernie, 2013) and extensive existing data (Fraixedas et al, 2020), are often chosen as indicators for studying large-scale ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Such biogeographic distribution patterns in birds are known to be correlated to the trophic niche breadth (Fargallo et al, 2022). However, our further investigation on geographic distinctness of desert through mapping avian biodiversity with observational data, revealed that trophic niches not only play a crucial role in determining regional diversity but also the influx of migratory species (Mukherjee et al, 2024). These migratory birds due to their wide distribution (Pereira and Cooper, 2006), sensitivity to environmental changes (Smits and Fernie, 2013) and extensive existing data (Fraixedas et al, 2020), are often chosen as indicators for studying large-scale ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%